THE HARVESTING OF HIGH LIPID CONTENT MICROALGAE BIOMASS THROUGH A FLOCCULATION STRATEGY - Lemos, J. S.; Vargas, J. V. C.; Mariano, A. B.; Kava, V. M.; Klein Jr, J. O.; Ordonez, J. C. (Revista de Engenharia Térmica, 2018)
Different flocculants were evaluated for the flocculation of microalgae biomass of Acutodesmus obliquus. Flocculation was tested with FeCl3 and NaOH at different concentrations and compared to a sample centrifuged at 7000 rpm. The evaluated parameters were absorbance (540 nm) in the clarified medium, and lipids concentration. For FeCl3 (0.2 mmol L-1) as flocculant, efficiency was 96.8%, and with NaOH (8 mmol L-1) 93.5%. Centrifugation efficiency was lower than with either flocculants: 91.7%. However, NaOH flocculation reduced lipid content, which did not occur with FeCl3. Flocculation efficiency was affected by salt concentration, reducing efficiency by 79% due to increased nutrient concentration (9 mL L-1).